HUBUNGAN STATUS GIZI, ASUPAN ENERGI, DAN STATUS HIDRASI DENGAN TINGKAT KEBUGARAN PADA REMAJA LAKI - LAKI USIA 10 - 17 TAHUN DI SSB ASTAM - Rif'atul Awwaliyah, (2020)
Background : Indonesian football achievements still relatively low category. August 2018 Indonesia was ranked 164th, in February 2019 Indonesia was ranked 159th, and in October 2019 Indonesia was ranked 171th out of 211 FIFA member countries (FIFA, 2019). One of the causes of underachievements of Indonesian football is the low fitness level in Indonesia soccer athletes (Martony, et al., 2013). Objective : This study aims to determine the relationship between nutritional status, energy intake, and hydration status with fitness levels on male adolescent aged 10-17 years in SSB ASTAM. Method :This study used a cross-sectional design with 50 samples of soccer athletes aged 10-17 years in SSB ASTAM. Nutritional status data is taken by anthropometric measurements, which are measuring body weight and height of a soccer athlete, energy intake data is taken using the interview Food Recall 3x24 hours method, and hydration status data by checking urine color using the PURI method (Check Your Own Urine), and fitness level data was taken using the cooper test method. Result : The analysis shows that there is a relationship between nutritional status (p=0,016), energy intake (p=0,025), and hydration status (p=0,016) with fitness level in soccer athletes SSB ASTAM . Researchers suggest conducting nutrition counseling to athletes and parents as well as to have a good relationship and communication with PSSI to improve the level of fitness in SSB ASTAM soccer athletes and youth athlete coaching programs can run well